Perubahan Hasil Belajar Faktor dan Kelipatan Siswa Sekolah Dasar dengan Pendekatan PMRI - Ananda, Vinda Dwi; Fitria, Yanti; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research is aimed to find  the effect of Indonesian realistic mthematics education (PMRI) approach on factors and multiple becoming outcomes in students grade IV SD Gugus III Kecamatan Payakumbuh Barat.. This research is quasi-experimental research with nonequivalent control group design. The sample was taken by using cluster sampling technique and the sample are students in class IV SDN 09 Payakumbuh which consistsof two classes, 28 students in IVA and 28 students in IVB . The results of the calculation of the research data used are t-test obtained by t count 2.2236> t table 2.0048 at the level of α 0.05. It can be concluded that there is a significant effect PMRI approach on factors and multipleslearning outcomes in Class IV SD Gugus III Kecamatan Payakumbuh Barat.Keywords : PMRI Approach, Learning Outcomes, Factors and Multiples